Profile and Income of Bali Cattle Farmers under Different Farming Systems in Southeast Sulawesi, Indonesia - Sulfiar, Ahmat Endang Two; Agustin, Citravia; Nugroho, Tristianto (Universitas Halu Oleo, 2022)
The farmers in Southeast Sulawesi, Indonesia have started using the intensive farming system for Bali Cattle rearing in recent decades. This study aimed to determine the profile and income of Bali Cattle farmers under intensive, semi-intensive, and extensive farming systems in Southeast Sulawesi, Indonesia. The research was conducted using the Participatory Rural Appraisal (PRA) method. Profile and income data were collected from 105 farmers selected by purposive sampling. The analytical model used is one-way ANOVA with the farming system as a factor. The results showed that the age of intensive farmers was younger (p<0.05) and had a lower experience of raising livestock (p<0.05) than extensive and semi-intensive farmers. In addition, farmers in the intensive farming system have a higher goal of raising livestock as fertilizer producers (p<0.05) than extensive and semi-intensive. However, semi-intensive and extensive farming systems had a higher average number of cows, net body weight production yield, income, and value-added (p<0.05) than the intensive farming system. Based on the results, it can be concluded that semi-intensive and extensive farming systems generate high incomes and can be more economically sustainable than intensive systems.Keywords: participatory rural appraisal, animal production system, farming system